Efficacy and Safety of Deferiprone for Parkinson’s Disease: A Systematic Review and Meta-Analysis of Motor Function and Overall Disease Severity - Ehab, Menna; Ibrahim, Ismail A.; Hekal, Rawan Gameel; Solah, Israa A.; Ezz-Alarab, Moaz; Elewa, Mandy; Zidat, Ayham R. A. (Springer-Verlag Italia SRL, 2026)
Background The accumulation of iron in brain regions is one of the characteristics of Parkinson's disease (PD). Deferiprone (DFP) is an iron chelator that reduces iron overaccumulation in certain diseases. The efficacy and safety of DFP in the management of PD have been assessed; however, the results remain controversial. Method A systematic review and meta-analysis were conducted in accordance with PRISMA guidelines. A comprehensive search was conducted across five databases to identify all randomized clinical trials and observational studies. The primary outcomes included changes in motor function (MDS-UPDRS III) and overall disease severity (MDS-UPDRS total score). Additionally, the safety of DFP was assessed by analyzing adverse events. A network meta-analysis using a random-effects model was conducted. Results Four randomized clinical trials were identified. The studies included 567 patients with early-stage PD. The DFP doses across the included studies ranged from 3.75 to 15 mg/kg twice daily. None of the doses showed a significant Improvement in motor function (I2 = 0%), or in overall disease severity (I2 = 82.5%), compared with placebo in the network analysis. However, a non-significant improvement in motor function was observed at 7.5 mg/kg twice daily, whereas higher doses were associated with worsening clinical scores. Adverse events were generally mild, although there were some safety concerns at higher doses. Conclusion DFP can reduce accumulated iron across brain regions. However, current evidence does not support the use of DFP for the clinical and symptomatic management of PD within the assessed range of doses and treatment periods.
Keywords: Deferiprone; Meta-analysis; Neurodegeneration; Iron Chelation Therapy; MDS-UPDRS; Parkinson’s Disease